A hard, wear-resistant, electrically conductive coating and a method for making the same

CN122875770APending Publication Date: 2026-10-09CHINA YANGTZE POWER
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611037346.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,致密涂层的微观结构缺乏连续导电通路,电流传输需依赖硬质合金基体自身的导电性,而铁基合金的导电率通常不足5%IACS,导致涂层的整体导电性能不佳

Benefits of technology

本发明创造通过针对性解决现有技术核心缺陷,依托多维度技术改进实现多重优势,具体体现为:采用“多孔硬质骨架协同导电填充相”的复合结构设计,Fe-Cr-B-Si系合金骨架经SLM技术制备形成CrB、Fe3B硬质相及马氏体基体,硬度可达700~800 HV,有效弥补了单一导电材质耐磨性不足的缺陷;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875770A_ABST
    Figure CN122875770A_ABST
Patent Text Reader

Abstract

The application discloses a kind of hard wear-resistant conductive coating and its preparation method include: (1) using SLM technology, with Fe-Cr-B-Si series alloy powder as raw material, porous hard skeleton is prepared on the surface of steel matrix, the porous hard skeleton has three-dimensional connected pore structure, porosity is 20~30%, pore size is 5~15 μm;(2) porous hard skeleton is together with matrix and is preheated at 800~1050 ℃ for 20~40 min;The raw material of conductive filling phase is melted, and the liquid conductive filling phase is obtained;(3) porous hard skeleton and matrix are placed in 1100~1200 ℃ environment, and the liquid conductive filling phase is poured into the pore of porous hard skeleton, and graphite cover is covered after pouring is completed;(4) the coating after pouring and matrix are cooled to room temperature with furnace at the rate of 15~25 ℃ / min;(5) the surface of the coating after cooling is polished, so that the surface of conductive filling phase is flush with the surface of skeleton.The application prepares composite coating with hard wear-resistant structure and conductive performance, guarantees the stability and life of current collector ring long-term service.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material surface modification technology, specifically to surface strengthening technology for current-carrying friction pairs such as slip rings, and particularly to a hard, wear-resistant, conductive coating and its preparation method. Background Technology

[0002] As a core conductive component in rotating electrical equipment such as motors and generators, the slip ring's surface current-carrying friction pair must withstand the dual effects of high-speed sliding friction from the brushes and continuous high-current transmission over extended periods, resulting in extremely harsh operating conditions. On one hand, the long-term mechanical friction between the brushes and the slip ring surface leads to progressive wear of the coating material. Accumulated wear increases contact resistance, causes localized heating, and in severe cases, can even cause equipment shutdown. On the other hand, stable current transmission requires the coating to possess excellent conductivity to reduce power transmission losses and ensure equipment operating efficiency. Therefore, the slip ring surface coating must simultaneously possess high hardness and wear resistance as well as excellent conductivity; the synergistic effect of these two properties directly determines the slip ring's service life and the equipment's operational stability.

[0003] Existing technologies for strengthening the current-carrying friction pair on the surface of slip rings have three key drawbacks, each directly affecting the slip ring's performance and application scenarios: First, traditional laser selective melting coating structures, often prepared using Fe-Cr-B-Si series hard alloy powders, can form a high-hardness, wear-resistant layer that effectively resists brush friction. However, the dense coating's microstructure lacks continuous conductive pathways, resulting in poor conductivity. This makes it difficult to balance the dual requirements of the current-carrying friction pair for a wear-resistant hard structure and a continuous conductive phase, failing to resolve the technical contradiction between the two. Consequently, the slip ring may experience localized heating due to insufficient conductivity or premature failure due to inadequate wear resistance. Second, single-conductive material forming layers, while relying on the high conductivity of pure copper to meet current transmission requirements, suffer from limitations in hardness. The silver-based composite powder has significantly lower conductivity than cemented carbide, resulting in severe wear resistance. Under long-term friction with the brush, the formed layer is prone to significant wear failure. This not only shortens the replacement cycle of the slip ring but also increases the contact gap with the brush due to surface wear, leading to unstable conductive contact and affecting the overall operating accuracy of the equipment. Thirdly, some solutions for high-conductivity applications such as high-frequency motors use silver-based composite powder for laser selective melting. Although the addition of silver can further improve conductivity, silver is a precious metal, and its raw material cost is much higher than that of copper-based powder. Moreover, the fluidity of silver-based composite powder is poorly compatible with laser selective melting and subsequent filling processes, requiring additional optimization of process parameters. This significantly increases the cost and complexity of large-scale industrial production, limiting its widespread application.

[0004] Currently, existing technologies for surface strengthening of slip rings in the industry mainly fall into two categories. The first category involves using Selective Laser Melting (SLM) technology to prepare dense cemented carbide coatings, commonly using Fe-Cr-B-Si alloy powders as the forming raw material. After laser melting, this type of coating forms hard phases such as CrB and Fe3B, as well as a martensitic matrix, in its microstructure, achieving a hardness of 700-800 HV, effectively resisting long-term friction and wear from the brush. However, the microstructure of this dense coating lacks continuous conductive pathways, and current transmission relies on the conductivity of the cemented carbide matrix itself. Since the conductivity of iron-based alloys is typically less than 5% IACS, the overall conductivity of the coating is poor. The second category involves directly forming coatings with a single conductive material such as pure copper, relying on the excellent conductivity of pure copper (approximately 100% IACS) to meet the current transmission requirements. However, pure copper has extremely low hardness (approximately 40~60HV) and severely insufficient wear resistance. Under long-term friction with the brush, the coating surface is prone to significant wear failure, which not only shortens the replacement cycle of the slip ring, but also increases the contact gap with the brush due to surface wear, leading to unstable conductive contact.

[0005] Furthermore, Chinese patent document CN108907214A discloses a method for preparing porous tungsten-rhenium alloy porous parts using SLM technology, with a porosity of 30%~35%. Other prior art discloses a scheme for preparing a porous tungsten framework using SLM technology and then infiltrating it with copper to prepare a tungsten-copper composite material. This scheme combines the high-temperature characteristics of tungsten with the high conductivity of copper to obtain a bulk composite material with both high-temperature resistance and electrical conductivity. However, the above schemes all use independent bulk materials or parts as the preparation object, rather than constructing a composite structure on the surface of a steel substrate in the form of a coating. Meanwhile, existing research has used Fe-Cr-B-Si alloy powders for preparing wear-resistant coatings using laser cladding technology, but these coatings all have dense structures without pre-reserved conductive channels, thus failing to achieve the desired conductivity. For the surface coating of the collector ring, its thickness is typically only 100~150μm, falling into the category of thin coatings. Achieving precise composite of the hard, wear-resistant phase and the conductive phase at such a thin scale presents completely different technical challenges in terms of thermal matching, interfacial bonding, and filling uniformity compared to bulk materials.

[0006] In summary, existing technologies lack a technical solution that can integrate a hard, wear-resistant structure with a continuous conductive channel on a steel substrate surface using a coating. How to construct a high-hardness, wear-resistant skeleton to resist frictional loss while simultaneously establishing a continuous and stable conductive path to ensure current transmission within a 100-150 μm thick coating, and ensuring a strong bond between the skeleton and the filler phase, as well as between the coating and the substrate, is a pressing technical challenge in this field. This invention addresses these problems by constructing a Fe-Cr-B-Si alloy porous hard skeleton with a three-dimensional interconnected pore structure on the steel substrate surface, and filling the pores with a conductive filler phase. This achieves a three-dimensional interpenetrating network composite of the hard, wear-resistant skeleton and the conductive channel at the coating scale, thereby simultaneously satisfying the dual requirements of wear resistance and conductivity for the slip ring. Summary of the Invention

[0007] This invention addresses the technical contradiction in existing technologies where it is difficult to simultaneously achieve wear resistance and conductivity in the surface coating of collector rings. It provides a hard, wear-resistant, and conductive composite coating and its preparation method. By constructing a three-dimensional interconnected Fe-Cr-B-Si alloy porous hard skeleton on the surface of a steel substrate and filling the pores with a conductive filler phase, the wear-resistant skeleton and conductive channels are integrated into a composite. This allows the coating to simultaneously possess high hardness and wear resistance as well as excellent conductivity, meeting its long-term service requirements.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing a hard, wear-resistant, and conductive composite coating, comprising the following steps: (1) Using selective laser melting (SLM) technology, a porous hard skeleton is prepared on the surface of a steel substrate using Fe-Cr-B-Si alloy powder as raw material. The porous hard skeleton has a three-dimensional interconnected pore structure with a porosity of 20%~30% and a pore size of 5~15 μm. (2) The porous rigid framework prepared in step (1) together with the matrix is ​​preheated at 800~1050 ℃ for 20~40 min; the raw materials of the conductive filling phase are melted to obtain a liquid conductive filling phase. During the melting process, a quartz glass rod is used to stir gently to avoid local overheating, ensure that its composition is uniform and has good fluidity, and avoid oxidation from affecting the filling effect. (3) Place the porous rigid framework and the substrate in a condition of 1100~1200 ℃, and pour the liquid conductive filling phase obtained in step (2) into the pores of the porous rigid framework. After pouring, cover with a graphite cover plate. (4) Cool the cast coating and substrate to room temperature in the furnace at a rate of 15~25 °C / min; (5) Polish the surface of the cooled coating to make the surface of the conductive filler phase flush with the surface of the skeleton.

[0009] In the preferred embodiment, in step (1), the chemical composition of the Fe-Cr-B-Si alloy powder by mass percentage is: Cr 12%~15%, B 2%~3%, Si 1%~2%, C 0.3%~0.5%, with the balance being Fe; the powder particle size is 30~50 μm, D50=40μm, and the particle size distribution is uniform.

[0010] In the preferred embodiment, the process parameters for laser selective melting in step (1) are as follows: dot matrix scanning, laser power 200~300W, spot diameter 70~100 μm, scanning speed 500~800 mm / s, scanning spacing 90~120 μm, and single-layer thickness 45~65 μm. Argon gas protection is used throughout the process; high-pressure argon gas is used to purge unmelted powder from the pores to reduce residual moisture in the pores.

[0011] In the preferred embodiment, in step (1), the steel substrate is any one of Q235, Q355, 16Mn or 20# steel; the substrate is subjected to progressive sanding, ultrasonic cleaning and drying treatment before the skeleton is prepared.

[0012] In a further preferred embodiment, the sandpaper is used for progressive polishing, with 400, 800, 1200, 1800, 2000, and 2500 grit sandpaper used in sequence.

[0013] In a further preferred embodiment, the ultrasonic cleaning uses a cleaning solution of ethanol and deionized water in a volume ratio of 1:1, and the ultrasonic cleaning time is 20-40 minutes.

[0014] In a further preferred embodiment, the drying process involves a drying temperature of 75-85 ℃ and a drying time of 1.5-2.5 h.

[0015] In the preferred embodiment, in step (1), the thickness of the porous rigid skeleton is 100~150 μm.

[0016] In the preferred embodiment, in step (2), the porous rigid skeleton is ultrasonically cleaned with anhydrous ethanol for 15-20 minutes before preheating and dried with hot air at 75-85 ℃.

[0017] In the preferred embodiment, in step (2), the raw material of the conductive filling phase is any one of copper, tin bronze, chromium copper or chromium zirconium copper.

[0018] In the preferred embodiment, the melting treatment of the conductive filling phase in step (2) is specifically as follows: the conductive filling phase is placed in a graphite crucible of a medium-frequency induction melting furnace, and 0.5~2 L / min of argon gas is introduced as a protective atmosphere. The temperature is raised to 1150~1200 ℃ and held for 10~15 min to remove gas and impurities. During the melting process, a quartz glass rod is used to gently stir the liquid conductive filling phase to avoid local overheating, ensure that its composition is uniform and has good fluidity, and avoid oxidation from affecting the filling effect.

[0019] In the preferred embodiment, in step (3), the casting is carried out using a high-density annular graphite mold that matches the planar dimensions and thickness of the porous rigid skeleton to achieve directional filling. The gap between the inner wall of the mold and the edge of the porous rigid skeleton is controlled at 0.1~0.2mm. The bottom is sealed with high-temperature ceramic sealant with a temperature resistance of ≥1300℃ to prevent liquid copper leakage. The porous rigid skeleton is kept in a preheated state of 800~1050℃. The liquid conductive filler phase with a stable temperature of 1150~1200℃ is slowly poured along the inner wall of the mold at a flow rate of 0.5~2mL / s. When the liquid level is flush with the top of the mold, the pouring is stopped. The top of the mold is immediately covered with a graphite cover plate to reduce contact with air and maintain a local heat preservation environment.

[0020] In the preferred embodiment, in step (5), the polishing process is performed using 200-400 grit sandpaper.

[0021] In a further preferred embodiment, in step (5), the grinding process is to first use 200-400 grit sandpaper for grinding, then use a diamond grinding wheel for fine grinding, and finally use diamond polishing paste for polishing. After polishing, use anhydrous ethanol for ultrasonic cleaning for 3-10 minutes to remove the debris and impurities remaining from the grinding and polishing process, ensuring that the surface is clean and smooth.

[0022] In a preferred embodiment, the composite coating has a conductivity ≥20% IACS and a hardness ≥500 HV.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention addresses the core defects of existing technologies by targeting them, and achieves multiple advantages through multi-dimensional technological improvements. Specifically, it adopts a composite structure design of "porous hard skeleton synergistic conductive filling phase". The Fe-Cr-B-Si alloy skeleton is prepared by SLM technology to form CrB, Fe3B hard phase and martensitic matrix, with a hardness of up to 700~800 HV, which effectively makes up for the lack of wear resistance of single conductive materials. The preferred filler phase is pure copper, which has both good conductivity and moderate plasticity. After being melted under the protection of an inert atmosphere, it has high purity and excellent fluidity. It not only ensures stable current transmission by utilizing its own conductivity, but also buffers the impact of the brush through plasticity, avoiding excessive wear of the brush by the hard skeleton. It forms a solid metallurgical bond with the Fe-Cr-B-Si skeleton, successfully solving the technical contradiction of traditional dense coatings that are "wear-resistant but not conductive, or conductive but not wear-resistant".

[0024] The filling process innovatively adopts an integrated process of inert atmosphere-protected melting and high-density graphite mold directional impregnation casting: During the melting stage, argon (0.5~2 L / min) is used as the protective atmosphere, and the temperature is held at 1150~1200 ℃ for 10-15 min to complete degassing and impurity removal, ensuring that the liquid copper composition is uniform and free from oxidation pollution; During the casting stage, a customized graphite mold (with a gap of 0.1~0.2mm between the inner wall and the coating) is used to achieve directional filling and precise volume matching. The high-temperature ceramic sealant (temperature resistance ≥1300℃) sealing design prevents leakage. The operation of slowly pouring liquid copper at 1150~1200℃ at a flow rate of 0.5~2mL / s and the graphite cover plate keeping it warm in real time effectively avoids splashing and air entrapment problems. High filling rate can be achieved without complex vacuum auxiliary equipment, which simplifies the process, reduces equipment investment costs, and avoids the degradation of conductivity and wear resistance caused by pore voids from the source.

[0025] The solidification and post-treatment process employs a slow furnace cooling process at 20 ℃ / min to completely eliminate thermal stress generated by rapid cooling and prevent coating cracking. Combined with fine finishing with 200~400 grit sandpaper, it ensures that the surface of the filler phase is flush with the hard skeleton, guaranteeing the overall structural stability of the composite coating. At the same time, pure copper raw materials are cost-effective and highly compatible with the porous skeleton process prepared by SLM, making them more valuable for industrial application compared to precious metal-based filler materials. Ultimately, the slip ring achieves a synergistic performance of "high hardness and wear resistance, high conductivity and low brush wear", taking into account both technological advancement and practical application versatility. Attached Figure Description

[0026] Figure 1 This is a structural diagram of the high conductivity and wear-resistant coating prepared according to an embodiment of the present invention.

[0027] Figure 2 This is a top view of the preparation of a high-conductivity and wear-resistant coating according to an embodiment of the present invention. Detailed Implementation

[0028] The purpose of this invention is to solve the problem of balancing wear resistance and conductivity on the surface of traditional collector rings. By constructing a porous rigid skeleton and then filling it with a conductive filler phase to prepare a composite structure, a synergistic improvement in wear resistance and conductivity can be achieved.

[0029] The following examples illustrate this. Figure 1Taking a current collector ring substrate made of any one of Q235, Q355, 16Mn, or 20# steel as an example, the present invention will be further described in detail through specific embodiments. All raw materials used in the embodiments can be commercially available or prepared using conventional methods.

[0030] Example 1 A method for preparing a hard, wear-resistant, and conductive composite coating includes the following steps: S1. Pretreatment process of the slip ring substrate: The core of the pretreatment is to remove impurities from the substrate surface and optimize the surface flatness, laying the foundation for the subsequent firm bonding between the porous rigid skeleton and the substrate. The specific operation and parameters strictly follow the following steps: S101. Surface polishing: The surface of the collector ring substrate to be clad is polished step by step using 400, 800, 1200, 1800, 2000 and 2500 grit sandpaper to ensure that the surface roughness of the substrate meets the requirements of powder spreading and bonding in the SLM process. S102. Ultrasonic cleaning treatment: The polished collector ring substrate is completely immersed in an ultrasonic cleaning tank. The cleaning tank is prepared with a mixture of ethanol and deionized water (volume ratio 1:1). This ratio can simultaneously dissolve oil and remove oxide scale. The ultrasonic cleaning time is set to 30 minutes to remove cutting debris, rolling oil and oxide scale attached to the substrate surface. S103. Drying and Storage: Remove the ultrasonically cleaned substrate from the cleaning tank, gently wipe off excess cleaning solution with a lint-free cotton cloth, and then place it in a forced-air drying oven for drying at 80℃ for 2 hours. This quickly removes moisture from the substrate surface while preventing oxidation caused by excessive temperature. After drying, immediately transfer the substrate to a dry, clean, sealed container for later use to prevent it from absorbing moisture or dust from the air during storage, thus avoiding a decrease in the bonding strength of the skeleton due to pores and impurities caused by moisture evaporation during subsequent SLM preparation. S2. Porous Hard Skeleton Fabrication Process: A porous hard skeleton is fabricated using selective laser melting (SLM) technology. The material selection, process parameter settings, and post-processing of the porous hard skeleton are all centered on "ensuring wear resistance and reserving filling space." The specific steps are as follows: S201. Selection and Characteristic Control of Porous Hard Skeleton Material: Fe-Cr-B-Si alloy powder is selected as the porous hard raw material. The chemical composition (mass fraction) of this alloy powder is strictly controlled as follows: Cr 12%~15%, B 2%~3%, Si 1%~2%, C 0.3%~0.5%, with the balance being Fe. The powder particle size range is 30~50μm to ensure uniform particle size distribution (D50=40μm), ensuring uniform spreading and full melting of the powder in the SLM process, avoiding uneven powder spreading or incomplete fusion defects caused by poor powder flowability. After selective laser melting, the alloy will form hard phases such as CrB and Fe3B in the microstructure, and the matrix structure is martensite. The final overall hardness of the skeleton can reach 700HV by Vickers hardness tester, which has excellent wear resistance to resist long-term friction of the brush. S202. Selective Laser Melting (SLM) Process Parameter Settings: A dot-matrix scanning strategy is adopted (the scanning path is an orthogonal dot matrix, and the center-to-center distance between adjacent dots matches the scanning distance). The preset pore structure is achieved by precisely controlling the process parameters. The specific parameters and working principle are as follows: The parameters of the selective laser melting technology used are as follows: Laser power: 250 W. Too low a power will result in insufficient melting of Fe-Cr-B-Si alloy powder, leading to incomplete fusion defects; too high a power will cause the matrix to overheat and deform, and may also cause excessive melting of powder, resulting in pore blockage. The spot diameter is 80 μm. The spot size is calibrated by a laser marking machine to ensure that the spot circularity is ≥90%. This diameter can accurately control the cladding area and avoid overfilling of pores caused by an excessively large spot. Scanning speed: 650 mm / s. The scanning speed and laser power work together to control the energy density of the molten pool. If the speed is too low, the molten pool will overheat, resulting in coarse grains and affecting the toughness of the skeleton. If the speed is too high, the molten pool will have a short existence time and the powder will not melt completely. Therefore, it is necessary to maintain a match between power and speed. Scanning distance: 100 μm. This parameter directly determines the pore distribution and porosity. The larger the scanning distance, the larger the unmelted area between adjacent melt channels and the higher the porosity. By adjusting the scanning distance, a porous structure with a pore size of 5~15 μm and a porosity of 20%~30% can be finally prepared. Single-layer coating thickness: 45-65 μm. Too thin a single layer will reduce process efficiency, while too thick a single layer will easily lead to poor interlayer bonding. During the preparation process, following the above single-layer thickness parameters, the powder spreading, laser scanning melting, and platform descent cycles are repeated, accumulating layer by layer until the preset total skeleton thickness is reached. Total thickness of the skeleton: 110 μm, adjusted according to the service conditions of the slip ring - the upper limit of the thickness is taken for severe wear conditions, and the lower limit of the thickness is taken for mild wear conditions, to avoid the skeleton being worn through due to excessive thickness, or the substrate being increased due to excessive thickness. Protective gas: High-purity argon (99.99% purity) is used at a flow rate of 12 L / min, precisely controlled by a gas flow meter. Argon enters through the inlet of the SLM equipment and exits through the outlet, creating a sealed protective atmosphere to isolate the alloy powder and molten pool from air during the preparation process, preventing oxidation products from affecting the hardness and bonding strength of the framework. Finally, high-pressure argon is used to purge unmelted powder from the pores to reduce residual moisture. S203. Post-processing of porous rigid skeleton: After the porous rigid skeleton is prepared, it is immediately pre-treated to ensure the subsequent filling effect: Step 1: For the porous rigid skeleton prepared by SLM technology, i.e., the rigid Fe-Cr-B-Si coating skeleton, ultrasonic cleaning with anhydrous ethanol for 15 min is used to remove residual powder particles on the surface; Step 2: Hot air drying, the cleaned rigid Fe-Cr-B-Si coating and the substrate are placed in an 80 ℃ forced air drying oven and dried until there are no obvious water stains on the surface; Step 3: Low temperature preheating, the dried components are placed in a box-type resistance furnace and preheated at 800~1050 ℃ for 30 min to reduce the temperature difference between the subsequent liquid filling phase and the coating, and at the same time reduce residual water vapor in the pores to avoid the formation of pores during casting; after preheating, the furnace is kept at a constant temperature, waiting for casting. S3. Selection and Melting Process of Conductive Filler Phase: The conductive filler phase must simultaneously meet three requirements: high conductivity, fluidity, and compatibility with the framework. In this embodiment, pure copper is used as the filler material, and its purity and performance are ensured through melting under an inert atmosphere. The specific steps are as follows: S301. Raw material selection: Pure copper is selected as the melting raw material to ensure that the raw material is free of obvious oxide scale and impurities, and to ensure the purity and fluidity of the molten liquid metal. S302. Melting Equipment and Protective Atmosphere: A medium-frequency induction melting furnace is used, equipped with a graphite crucible (high temperature resistant, poor wettability with liquid pure copper, facilitating subsequent demolding and metal purity control); high-purity argon gas is introduced as a protective atmosphere throughout the melting process, with an argon gas flow rate of 6 L / min, precisely controlled by a gas flow meter to isolate air and prevent oxidation of the liquid metal; S303, Melting Parameter Control: Heating Stage: After placing pure copper into the graphite crucible, start the melting furnace and gradually raise the temperature to 1150~1200 ℃; Heating and Impurity Removal: Hold at 1150~1200 ℃ for 15 min, during which time the liquid copper is gently stirred with a quartz glass rod to avoid local overheating, while promoting the floating and separation of gases and impurities in the molten metal to achieve degassing and impurity removal; Temperature Stabilization: After the holding period, stabilize the temperature of the liquid copper at 1150-1200 ℃ to ensure that it has good fluidity and meets the requirements for impregnation and filling; S304. Melting quality verification: Visually inspect the color and fluidity of the liquid copper to ensure that the molten metal has no obvious oxide slag or bubbles and has good fluidity before subsequent pouring can proceed. S4. Conductive Filler Phase Impregnation and Casting Process: High-density graphite mold directional constraint and impregnation casting technology are used to achieve full filling of pores and precise volume matching. The specific process steps and parameter control are as follows: 1. Mold customization and selection: High-density graphite is used to prepare the ring mold, which is customized according to the planar dimensions and thickness of the porous skeleton to ensure that the inner contour of the mold and the outer contour of the coating are perfectly matched; the gap between the inner wall of the mold and the edge of the coating is controlled at 0.2mm, which not only ensures positioning accuracy, but also avoids excessive gaps that may lead to liquid metal leakage.

[0031] 2. Mold Installation and Sealing: The customized graphite mold is fitted around the hard Fe-Cr-B-Si coating on the surface of the current collector ring substrate, ensuring that the mold height is consistent with the coating thickness to guarantee that the final filled surface is flush with the coating. The bottom of the mold and the surface of the substrate are sealed with high-temperature ceramic sealant with a temperature resistance of ≥1300 ℃ to ensure that it does not fail at the pouring temperature of the liquid conductive filler phase and to prevent leakage of the liquid conductive filler phase along the gap between the substrate and the mold. After sealing, the substrate assembly with the mold assembled is removed from the resistance furnace and quickly moved to the pouring station, keeping the preheating temperature of the skeleton not lower than 1000 ℃. 3. Immersion casting operation: Slowly pour molten copper, with the temperature stabilized at 1150~1200 ℃, along the inner wall of the graphite mold. Control the pouring flow rate at 0.5~2 mL / s. Use a guide channel to assist in pouring to avoid splashing or air entrapment of the molten metal. During the pouring process, observe the height of the molten copper level in real time. When the level is level with the top of the mold (i.e., the height of the coating surface), stop pouring immediately. After pouring, quickly cover the top of the mold with a graphite cover plate to reduce the contact between the molten copper and air, while maintaining a local heat preservation environment to prevent the molten metal from cooling suddenly and affecting the filling effect. S5. Slow cooling in the furnace: Immediately place the cast components (including the substrate, frame, and mold) into a box-type resistance furnace and slowly cool them to room temperature at a rate of 20 ℃ / min. This cooling rate can completely eliminate the thermal stress generated by rapid cooling and avoid cracking and peeling of the coating and substrate due to the difference in thermal expansion coefficients. S6. Post-processing: Through slow solidification and precise post-processing, the structural stability and surface quality of the composite coating are ensured. The specific steps and parameters are as follows: Demolding and cleaning: After the components have completely cooled to room temperature, remove the graphite mold; use a lint-free cloth with a small amount of anhydrous ethanol to clean the residual high-temperature ceramic sealant and a small amount of metal residue on the inner wall of the mold to avoid residual impurities affecting subsequent surface treatment; Surface finishing: The coating surface is polished with 200-400 grit sandpaper to remove any excess copper residue, ensuring the copper filler phase surface is flush with the Fe-Cr-B-Si coating skeleton surface. This guarantees a smooth composite coating surface free of bumps, depressions, or other defects. Following the 200-400 grit sandpaper polishing, a diamond wheel is used for fine grinding, followed by polishing with diamond polishing compound. After polishing, the surface is ultrasonically cleaned with anhydrous ethanol for 5 minutes to remove any remaining debris and impurities from the grinding and polishing processes, ensuring a clean and smooth surface. A top view is shown below. Figure 2 As shown.

[0032] Example 2 The preparation method of a hard, wear-resistant, and conductive composite coating is basically the same as that in Example 1, except that the conductive filler phase is QSn6.5-0.1 tin bronze. Since the melting point of tin bronze (about 900~1000 ℃) is lower than that of pure copper, the melting and casting temperature is adjusted to 1100~1150 ℃.

[0033] Tin bronze is harder than pure copper, but has lower electrical conductivity. Compared to Example 1, the composite coating shows a significant increase in hardness and wear resistance, with a hardness of 585 HV, but a decrease in conductivity to 20.2% IACS.

[0034] Example 3 A method for preparing a hard, wear-resistant, and conductive composite coating is basically the same as in Example 1, except that the conductive filler phase is a Cu-0.8Cr (chromium copper) alloy. Chromium copper alloy has both high strength and good conductivity, making it a preferred material for balancing conductivity and wear resistance.

[0035] The composite coating has a slightly higher hardness than Example 1, reaching 550 HV, and a conductivity of 31.6% IACS, which is slightly lower than Example 1 but better than Example 2, achieving a good trade-off between hardness and conductivity.

[0036] Example 4 A method for preparing a hard, wear-resistant, and conductive composite coating is basically the same as in Example 1, except that the conductive filler phase is a Cu-Cr-Zr (chromium-zirconium-copper) alloy. The chromium-zirconium-copper alloy adds trace amounts of zirconium to chromium-copper, further improving the strength and high-temperature softening resistance of the matrix through precipitation strengthening. The melting and casting temperature is controlled at 1150~1200 ℃.

[0037] Compared to Example 3, the overall mechanical properties of the composite coating are further optimized, with the hardness increased to 565 HV and the conductivity maintained at 29.8% IACS. This achieves further improvement in the material's resistance to deformation and wear resistance while maintaining excellent conductivity.

[0038] Comparative Example 1 The preparation method of a hard wear-resistant conductive composite coating is basically the same as that in Example 1, except that a conductive filler phase is not cast.

[0039] The coating has a hardness of about 450 HV. Although the skeleton material is hard, the presence of a large number of pores on the surface reduces its wear resistance and lowers its conductivity to 2.5% IACS. It relies solely on the iron-based alloy for conductivity, resulting in extremely poor conductivity.

[0040] Comparative Example 2 The preparation method of a hard wear-resistant conductive composite coating is basically the same as that in Example 1, except that the SLM scanning spacing is reduced from 110 μm to 80 μm.

[0041] Reducing the scanning spacing increases the overlap between adjacent melt channels, decreasing the skeletal porosity from 30% to approximately 18%. This means an increase in the proportion of the hard phase and a decrease in the proportion of the conductive phase in the composite material. The hardness reaches 680 HV, while the conductivity decreases to 18.3% IACS.

[0042] Comparative Example 3 The preparation method of a hard wear-resistant conductive composite coating is basically the same as that in Example 1, except that the raw material of the porous hard skeleton is tungsten.

[0043] Performance testing: Hardness testing: The composite coating was tested at multiple points using a Vickers hardness tester, and the average hardness was 520 HV, which meets the wear resistance requirements. Conductivity testing: The conductivity of the composite coating was tested using a conductivity tester. The conductivity was 33% IACS, which meets the requirements for stable current transmission. Appearance and structural inspection: The surface and cross-section of the composite coating are observed using an optical microscope to ensure that there are no defects such as pores, cracks, or unfilled voids, and that the filling phase is tightly bonded to the skeleton.

[0044] The hardness and conductivity test data of the above embodiments and comparative examples are shown in Table 1. Table 1

[0045] As can be seen from the data comparison in Table 1, the "porous rigid framework + conductive filler phase" composite structure adopted in this invention effectively solves the contradiction between hardness and conductivity. First, comparing Example 1 and Comparative Example 1, the conductivity of the unfilled framework (Comparative Example 1) is only 2.5% IACS, and the macroscopic hardness is artificially low at 450 HV due to the presence of porosity. However, after filling with pure copper (Example 1), the conductivity jumps to 33% IACS, and the hardness increases to 520 HV, demonstrating the decisive performance improvement effect of the filler phase. Second, comparing Example 1 and Comparative Example 2, although Comparative Example 2 increased the hardness to 680 HV by reducing the framework porosity (approximately 18%), the reduction in the proportion of the conductive phase caused the conductivity to drop to 18.3% IACS, lower than the preferred 20% IACS index of this invention. This conversely proves that the high porosity (approximately 30%) parameter set in this invention is key to ensuring high conductivity. Finally, a comparative analysis of Examples 1-4 revealed that different filler materials achieved precise performance control: Example 1 (pure copper) exhibited the highest conductivity (33% IACS), suitable for high current-carrying conditions; Example 2 (tin bronze) had the highest hardness (585 HV), emphasizing wear resistance; while Examples 3 (chromium copper) and 4 (chromium zirconium copper) maintained excellent conductivity (29.8%-31.6% IACS) while retaining high hardness (550-565 HV), achieving the optimal balance of overall performance. In conclusion, the present invention possesses excellent overall performance and flexible adaptability to various operating conditions.

[0046] After passing the final inspection, the finished slip ring is wrapped in rust-proof paper and stored in a sealed container to prevent surface oxidation during storage and ensure stable performance during service.

[0047] It should be understood that the above embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

Claims

1. A method for preparing a hard, wear-resistant, and conductive composite coating, characterized in that, Includes the following steps: (1) Using selective laser melting (SLM) technology, a porous hard framework is prepared on the surface of a steel substrate using Fe-Cr-B-Si alloy powder as raw material. The porous hard framework has a three-dimensional interconnected pore structure with a porosity of 20%~30% and a pore size of 5~15μm. (2) The porous rigid framework prepared in step (1) together with the matrix is ​​preheated at 800~1050℃ for 20~40min; the raw materials of the conductive filling phase are melted to obtain a liquid conductive filling phase; (3) Place the porous rigid framework and the substrate in a condition of 1100~1200℃, and pour the liquid conductive filling phase obtained in step (2) into the pores of the porous rigid framework. After pouring, cover with a graphite cover plate. (4) Cool the cast coating and substrate to room temperature in the furnace at a rate of 15~25℃ / min; (5) Polish the surface of the cooled coating to make the surface of the conductive filler phase flush with the surface of the skeleton.

2. The method for preparing the hard, wear-resistant, and conductive composite coating according to claim 1, characterized in that, In the preferred embodiment, in step (1), the chemical composition of the Fe-Cr-B-Si alloy powder by mass percentage is: Cr 12%~15%, B 2%~3%, Si 1%~2%, C 0.3%~0.5%, with the balance being Fe; the powder particle size is 30~50μm, and D50=40μm.

3. The method for preparing the hard, wear-resistant, and conductive composite coating according to claim 1, characterized in that, In step (1), the process parameters for laser selective melting are as follows: dot matrix scanning, laser power 200~300W, spot diameter 70~100μm, scanning speed 500~800mm / s, scanning spacing 90~120μm, and single-layer thickness 45~65μm. Argon gas protection is used throughout the process; high-pressure argon gas is used to purge unmelted powder from the pores to reduce residual moisture in the pores.

4. The method for preparing the hard, wear-resistant, and conductive composite coating according to claim 1, characterized in that, In step (1), the thickness of the porous rigid skeleton is 100~150μm.

5. The method for preparing the hard, wear-resistant, and conductive composite coating according to claim 1, characterized in that, In step (2), the raw material for the conductive filling phase is any one of copper, tin bronze, chromium copper, or chromium zirconium copper.

6. The method for preparing the hard, wear-resistant, and conductive composite coating according to claim 1, characterized in that, In step (2), the melting treatment of the conductive filling phase is specifically as follows: the conductive filling phase is placed in a graphite crucible of a medium-frequency induction melting furnace, 0.5~2L / min of argon gas is introduced as a protective atmosphere, the temperature is raised to 1150~1200℃ and held for 10~15min to remove gas and impurities, and the liquid conductive filling phase is gently stirred with a quartz glass rod during the melting process.

7. The method for preparing the hard, wear-resistant, and conductive composite coating according to claim 1, characterized in that, In step (3), the casting is carried out using a high-density annular graphite mold that matches the planar dimensions and thickness of the porous rigid skeleton to achieve directional filling. The gap between the inner wall of the mold and the edge of the porous rigid skeleton is controlled at 0.1~0.2mm. The bottom is sealed with high-temperature ceramic sealant with a temperature resistance of ≥1300℃ to prevent liquid copper leakage. The porous rigid skeleton is kept in a preheated state of 800~1050℃. The liquid conductive filler phase with a stable temperature of 1150~1200℃ is poured along the inner wall of the mold at a flow rate of 0.5~2mL / s. When the liquid level is flush with the top of the mold, the pouring is stopped and the top of the mold is immediately covered with a graphite cover plate.

8. The method for preparing the hard, wear-resistant, and conductive composite coating according to claim 1, characterized in that, In step (5), the polishing process is to use 200-400 grit sandpaper for polishing.

9. The method for preparing the hard, wear-resistant, and conductive composite coating according to claim 1, characterized in that, In step (5), the polishing process involves first polishing with 200-400 grit sandpaper, then fine grinding with a diamond wheel, and finally polishing with diamond polishing paste. After polishing, the surface is ultrasonically cleaned with anhydrous ethanol for 3-10 minutes to remove residual debris and impurities from the grinding and polishing processes, ensuring a clean and smooth surface. The composite coating has a conductivity ≥20% IACS and a hardness ≥500HV.

10. A hard wear-resistant conductive composite coating prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Molding method for tungsten-based parts

    CN108907214A